Asymmetric sovereign risk: Implications for climate change preparation - José Eduardo Gómez González; Jorge Uribe; Oscar M. Valencia (Inter-American Development Bank (IDB), 2024)
Climate change adaptation efforts are heavily dependent on a country's fiscal capacity and the associated costs of undertaking adaptation policies. The current accumulation of high debt levels in emerging and low-income developing countries, which are disproportionately affected by climate change, raises significant concerns. This study shows that sovereign risk, and hence funding costs for governments, exhibits significantly asymmetric reactions to its determinants across the conditional distribution of credit spreads. This aspect, previously overlooked in the literature, has relevant policy implications. Countries with elevated risk levels are disproportionately vulnerable to climate change compared to their lower-risk counterparts, especially in the short term. Notably, investing in climate change preparedness proves effective in mitigating vulnerability to climate change, in terms of sovereign risk, particularly for countries with low spreads and long-term debt (advanced economies), where readiness and vulnerability tend to counterbalance each other. However, for countries with high spreads and short-term debt, additional measures are essential as climate change readiness alone is insufficient to offset vulnerability effects in this case. Results also demonstrate that the actual occurrence of natural disasters is less influential than vulnerability to climate change in determining spreads.
Keywords: F34; G15; H63; Q51; Q54; 330; credit risk; disaster risk; nonlinear dynamics; panelquantile regressions; preparedness; sovereign risk; vulnerability